Pendidikan Karakter: Sebuah Tinjauan Historis - Matrapi, Matrapi (JOIES (Journal of Islamic Education Studies), 2017)
Character education begins with a discourse created by Homeros and Hesiodos (two brilliant poets). The discourse precisely arose during ancient Greece. Then, in the development of its history, character education was coined by a German pedadog named F. W. Foerster at the end of the 18th century. He is also dubbed as the initiator of character education that emphasizes the ethical-spiritual dimension in the process of forming personality. Whereas character education in Indonesia can be explored from various native Indonesian characters, namely Sundanese, Batak, Javanese and Madura customs. Besides that, it has been used as the first mission to realize the vision of national development. so that born policies on character education. These policies are Law Number 20 of 2003 concerning the National Education System and Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education.